MICRO-RNA AS DIAGNOSTIC MODALITY OF MAJOR DEPRESSIVE DISORDER - Ratu, Estyka (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Major Depressive Disorder (MDD) is a chronic mental health disorder, with suicidal ideation, but until now an exact diagnostic approach has not been found. For the limitations of the current diagnosis, such as subjective reports of patients or their families with mental status examinations, there is still a lack of objective diagnostic results. In this case, it is still a challenge for researchers. Neutropic factors, hypothalamic-pituitary-adrenal hormones (HPA), indicators of inflammation, and metabolic factors, were found to be novel biomarkers for MDD. However, these biomarkers show limited sensitivity and specificity. The most recent diagnostic development effort is the use of microRNA as a diagnostic modality approach for MDD. Methods – This study uses a qualitative method by collecting valid journals with certain inclusion and exclusion criteria. The keywords used were MDD, microRNA, and Diagnostic. There are journals used as the source of this literature review which come from valid scientific sources such as NCBI, ScienceDirect, and PubMed which were published in the last 10 years. Results – The results of the miRNA-124-3p expression test showed a significant difference between the healthy control group and the MDD patient group. The specificity and sensitivity of miRNA-221-3p, miRNA-451a, miRNA-34a-5p, and let-7d-3p showed high accuracy in the diagnosis of MDD. Discuss – The unknown etiology of MDD makes some patients have no results or significant progress of their depression in clinical settings which is contributed by gene regulatory pathway that shows high significance associated with neural function brain in depressive disorders such as apoptotic pathway, P13K-Akt signaling, axon guidance, neurotrophin signaling pathway, mTOR signaling pathway. Conclusion- The diagnostic effectiveness of miRNA in major depressive disorder can be significantly enhanced by using miRNA expression coding and has been proven by various tests. Therefore, this research is expected to be an innovation in diagnosing MDD for further research. Keywords: MDD, depression, microRNA, diagnostic